Corporate Social Responsibility and Market Performance of Listed Companies in Sri Lanka - Muraleetharan,P. (Jaffna Science Association, 2023)
Recognition is given to Corporate Social Responsibility (CSR) and Market performance (MP) in developed nations. Studies concerning CSR and Market Performance (CP) of firms are found to be lacking particularly in Sri Lanka. Consequent to the stated problem, the current study aims to examine the linkage between the variables through acknowledged methods. The study further identifies the trend in CSR disclosure and market performance as well as the level of importance given by firms on individual CSR dimensions over the past period of five years, starting from 2018 to 2022. A sample of thirty listed companies under CSE was utilized for the purpose of the present study. The financial aspect of firms was evaluated using the Price Earnings Ratio (PER) and Earnings per Share (EPS). The outcome of the study put forward that an insignificant relationship exists between CSR and market performance of listed companies in Sri Lanka. Furthermore, evidence suggests where CSR disclosure gives the impression of a slight growth, the MP increased significantly over the years. Moreover, the study establishes that the highest proportion of information disclosed in annual reports relates to CSR dimensions such as employee relations, community relation, environmental issue, product quality and diversity.
Keywords: Corporate social responsibility; Market performance and Earnings per share